1995
DOI: 10.1152/ajpheart.1995.268.6.h2202
|View full text |Cite
|
Sign up to set email alerts
|

Video microscopy of cerebrocortical capillary flow: response to hypotension and intracranial hypertension

Abstract: Although autoregulation of cerebral blood flow is well established, the response of cerebral capillary circulation to reduced cerebral perfusion pressure (CPP) is unclear. The objective of this study was to determine whether red cell flow velocity in individual capillaries of the cerebral cortex is maintained during acute decreases in CPP. Microcirculation of the superficial parietal cerebral cortex of adult barbiturate-anesthetized artificially ventilated rats was visualized using a new design of closed-perfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 0 publications
6
58
1
Order By: Relevance
“…These animals were anesthetized and surgically prepared as described in Surgical preparation. In addition, a closed cranial window was prepared over the right parietal cortex with techniques described previously (20). The rats were then transferred to the stage of an intravital microscope, paralyzed with 80 mg of gallamine, and artificially ventilated with a 30% O 2-70% N2 mixture.…”
Section: Methodsmentioning
confidence: 99%
“…These animals were anesthetized and surgically prepared as described in Surgical preparation. In addition, a closed cranial window was prepared over the right parietal cortex with techniques described previously (20). The rats were then transferred to the stage of an intravital microscope, paralyzed with 80 mg of gallamine, and artificially ventilated with a 30% O 2-70% N2 mixture.…”
Section: Methodsmentioning
confidence: 99%
“…Variability in vascular compliance may lead to variation in blood flow velocity. In one study for instance, blood flow velocity was measured by video microscopy using an injected fluorescent compound that labeled red blood cells [15]. Using video microscopy and frame-by-frame analysis, the authors observed that, during 5% CO 2 ventilation (i.e., hypercapnia, capillary flow velocity increased relative to normal breathing (i.e., normocapnia).…”
Section: Vascular Density and Vascular Compliance Varies Between Braimentioning
confidence: 99%
“…These studies show that the capillary bed in gray matter consists of arteriolar capillaries that feed into approximately twice the number of true capillaries, which are drained in turn by a reduced number of venous capillaries. True capillaries have heterogeneous flow lengths between 150 and 500 microns and RBC transit times of 100 -300 msec (36). Flows in arteriolar and venous capillaries are at least twice this speed (36), and "non-auto regulating thoroughfare capillaries," which represent nonexchange thoroughfare routes, have also been described (37).…”
Section: Discussionmentioning
confidence: 99%
“…True capillaries have heterogeneous flow lengths between 150 and 500 microns and RBC transit times of 100 -300 msec (36). Flows in arteriolar and venous capillaries are at least twice this speed (36), and "non-auto regulating thoroughfare capillaries," which represent nonexchange thoroughfare routes, have also been described (37). This structure supports the rapid delivery of blood to the exchange capillaries and is entirely in keeping with the behavior of the contrast bolus on DSCE-MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation